CHILDREN'S EMOTIONAL INTELLIGENCE: BUILDING A PANCASILA PROFILE THROUGH THE LENS OF EDUCATIONAL PHILOSOPHY IN EARLY CHILDHOOD EDUCATION PROGRAMS - Ni Luh Ika Windayani; I Wayan Suastra (UHN I GUSTI BAGUS SUGRIWA DENPASAR, 2024)
The research aims to explore the role of children's emotional intelligence in building a Pancasila profile through the lens of educational philosophy in early childhood education programs. The literature study method complemented by field studies was used as the main approach in this research; with the main focus on studies related to emotional intelligence, Pancasila and educational philosophy. This research explores the concept of children's emotional intelligence as an important factor in developing the values of Pancasila. Throughout literature analysis, this research identifies how aspects of emotional intelligence, such as emotion acknowledgment, divergence management and empathy, can assist children to comprehend and internalize the values of Pancasila. Using the lens of educational philosophy, this research explains the concept of comprehensive learning, promoting a better understanding of children's emotional intelligence in the context of the values of Pancasila. Furthermore, semi-structured interviews were used in the field study. Data were analyzed descriptively qualitatively. The findings of this research contribute to understanding how early childhood education programs can be an effective vehicle for building the profile of Pancasila through developing children's emotional intelligence. Practical implications include the development of an early childhood education programs curriculum that is more oriented towards emotional intelligence, teacher training that integrates the values of Pancasila in daily activities and learning approaches which coalesce aspects of educational philosophy.